Functioning of Conceptual Metaphor in Shaping Image of Iraq in Regional and Federal Media in Germany - L. N. Rebrina; L. H. M. A. Al-Khafaji (Научный диалог)
This comparative study examines the role of conceptual metaphorization as a means of shaping the image of Iraq in regional and federal media in Germany from 2019 to 2024. The analysis focuses on the frequency of metaphors, the magnitude and dominant features of the nominative field of metaphors, semantic and part-of-speech properties of metaphor representatives, and the salient characteristics of the country as components of its image, along with paradigmatic and syntagmatic relationships. It identifies both stable and variable patterns of metaphorization across the two groups of media. The study highlights recurring metaphors such as “Iraq as a Living Being,” “Iraq as an Incomplete Whole,” “Iraq as a Place of Uncontrolled Power,” “Iraq as a Warrior,” “Iraq as a Theater,” “Iraq as a Toy,” and “Iraq as a Refuge.” The findings conclude the effectiveness of conceptual metaphor as a tool for stereotyping; similarities in the composition of metaphors despite differences in their frequency and density across various German media; a predominance of complex, structural, and ontological metaphors; and the presence of compatible and coherent metaphors. Notably, there is an interdependence between the frequency and density of the nominative field of metaphors, with higher density observed in federal media; stability in terms of the part-of-speech affiliation of representatives and dominance of noun representatives; predominant overlap in the dominant features of nominative fields across different media groups; and the existence of metaphors with varying degrees of conventionality.